Wage Differential Compensation Can Women Be Economically Empowered? Empirical Evidence from South Asia - Wijayawardhana, Weerasekara Mudiyanselage Pasan; Siriwardhane, Dinesha (Technium Social Sciences Journal, 2022)
Purpose- This study investigates the responsiveness of South Asian women to wage increment at the macro level and examines the South Asian women’s sensitivity on compensating wage differentials in terms of economic empowerment of women in the South Asian region at the micro-level. Design/methodology/approach – In the macro level analysis, the model used annual time series data from four South Asian countries; Sri Lanka, India, Pakistan and Bangladesh over the period of 2000 to 2017. Micro-level analysis of the study was done with the use of primary data gained through a questionnaire survey from the same sample countries and it covers the economic advancement and power and agency dimensions of women’s economic empowerment. The women’s wage compensation sensitivity index (WWCSI) constructed based on the survey results was used to build up the relationship between wage differential compensation and women’s economic empowerment. Findings – According to the results of macro level analysis of this study, wage is a key determinant of female labor force participation. Findings of micro level analysis suggest that compensating wage differentials is a strong tool that can economically empower South Asian women. It further shows that estate females are less sensitive to wage differential compensation than rural and urban females. And educated females show greater sensitivity for wage differential compensation than non-educated females. This research also identified relatively low wage differential compensation sensitivity in terms of power and agency compared to the economic advancement dimension in women’s economic empowerment. Originality/value – These findings support the view that wage differential compensation is “gendered”, and therefore, requires a special program to economically empower females.